Keefektifan Media Komunikasi Visual Powerpoint dalam Menyampaikan Pembelajaran di Prodi Pendidikan Penyuluh Agama Semester 3 - Agnieska Natalia Hutabarat; Raikhapoor Raikhapoor (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
This study aims to evaluate the effectiveness of PowerPoint visual communication media in delivering learning in the Islamic Counseling Education Program during the third semester. With the increasing need for engaging and interactive teaching methods, PowerPoint was chosen as a tool to enhance student understanding and participation. The research method employed a qualitative approach with a descriptive design. Data were collected through classroom observations, interviews with lecturers and students, as well as analysis of the learning materials presented using PowerPoint. The research sample consisted of third-semester students and the lecturers teaching the courses. The results indicate that the use of PowerPoint significantly increasees students' interest and motivation to learn. The attractive visual features and structured information delivery help students comprehend the concepts being taught. Additionally, the interactions that occur during PowerPoint presentations contribute to enhancing student engagement in the learning process. However, the study also found that the effectiveness of PowerPoint is highly dependent on the lecturer's ability to design and deliver the material. Lecturers who are skilled in using PowerPoint can create a more dynamic and interactive learning environment. Therefore, training for lecturers in the use of digital learning media is highly recommended. In concusion, PowerPoint is an effective visual communication media for delivering learning in the Islamic Counseling Education Program, provided that its use is supported by adequate lecturer competencies. This study offers recommendations for enhancing lecturer training in the use of PowerPoint to achieve optimal learning outcomes.